Sperm length variation is linked to sexual ornamentation in male paper wasps - de Souza, André R.; Santos, Eduardo F. [UNESP]; Baptista, Camila F.; Dias, Glenda; Nascimento, Fábio S.; Lino-Neto, José (Taylor & Francis, 2022)
Diversification of sperm design is a common feature in animals. Considerable intra-individual variation has been detected even in species whose males produce a monomorphic sperm. The evolutionary forces that shape the variation in the gross morphology of these gametic cells are still not completely understood. Previous studies suggest that the intra-individual variation in sperm size reduces as a result of post-copulatory sexual selection. To our knowledge, for the first time, we provide evidence here that pre-copulatory sexual selection can also play a role. By studying the Neotropical paper wasp, Polistes simillimus, a monandrous species, we found reduced variation in sperm length in males bearing sexual ornamentation preferred by females. Besides, the female spermatheca contains a less variable sperm compared to that in the male seminal vesicles. Thus, the scope of selection, acting on this sperm trait, seems broader than previously acknowledged.
Keywords: female choice; melanin-based sexual ornamentation; Polistes; pre-copulatory sexual selection; social insect; sperm morphology